Phenotypic, Transcriptomic, and Metabolomic Signatures of Root-Specifically Overexpressed OsCKX2 in Rice - Yan, Huimin; Sun, Hongzheng; Jia, Xueying; Lv, Chuanwei; Li, Junzhou; Zhao, Quanzhi (Frontiers in Plant Science, 2021)
Cytokinins are crucial signaling molecules that regulate plant growth and development, and mainly synthesized in roots. OsCKX2 irreversibly degrades nucleobase cytokinins by encoding cytokinin oxidase/dehydrogenase to control grain production in rice. In this study, OsCKX2 was specifically overexpressed in roots using RCc3 promoter to investigate the effect of root-source cytokinins on the growth of rice. OsCKX2 overexpressed (OE) rice showed retarded growth with lower cytokinin levels and biomass production. Transcriptome analysis between OsCKX2 OE rice and wild type (WT) revealed differentially expressed genes (DEGs) associated with cell division, cell wall structure, phytohormone signaling, and assimilation and catabolism. Metabolome analysis indicated that a majority of differential primary metabolites, such as amino acids and organic acids, increased, while lipids decreased in OsCKX2 OE rice. Integration of transcriptomic and metabolomic data showed that several DEGs and differential metabolites were related to glycolysis and tricarboxylic acid cycle (TCA). To conclude, reduced cytokinin levels via root-specific overexpression of OsCKX2 resulted in developmental defects, which confirmed the importance of root-source cytokinins in plant growth and morphogenesis.